Uncoupled nitric oxide synthase activity promotes colorectal cancer progression - Asim Alam; Steven C. Smith; Sundaresan Gobalakrishnan; Mina McGinn; Vasily A. Yakovlev; Christopher S. Rabender (Frontiers in Oncology, 2023)
Increased levels of reactive oxygen/nitrogen species are one hallmark of chronic inflammation contributing to the activation of pro-inflammatory/proliferative pathways. In the cancers analyzed, the tetrahydrobiopterin:dihydrobiopterin ratio is lower than that of the corresponding normal tissue, leading to an uncoupled nitric oxide synthase activity and increased generation of reactive oxygen/nitrogen species. Previously, we demonstrated that prophylactic treatment with sepiapterin, a salvage pathway precursor of tetrahydrobiopterin, prevents dextran sodium sulfate–induced colitis in mice and associated azoxymethane-induced colorectal cancer. Herein, we report that increasing the tetrahydrobiopterin:dihydrobiopterin ratio and recoupling nitric oxide synthase with sepiapterin in the colon cancer cell lines, HCT116 and HT29, inhibit their proliferation and enhance cell death, in part, by Akt/GSK-3β–mediated downregulation of β-catenin. Therapeutic oral gavage with sepiapterin of mice bearing azoxymethane/dextran sodium sulfate–induced colorectal cancer decreased metabolic uptake of [18F]-fluorodeoxyglucose and enhanced apoptosis nine-fold in these tumors. Immunohistochemical analysis of both mouse and human tissues indicated downregulated expression of key enzymes in tetrahydrobiopterin biosynthesis in the colorectal cancer tumors. Human stage 1 colon tumors exhibited a significant decrease in the expression of quinoid dihydropteridine reductase, a key enzyme involved in recycling tetrahydrobiopterin suggesting a potential mechanism for the reduced tetrahydrobiopterin:dihydrobiopterin ratio in these tumors. In summary, sepiapterin treatment of colorectal cancer cells increases the tetrahydrobiopterin:dihydrobiopterin ratio, recouples nitric oxide synthase, and reduces tumor growth. We conclude that nitric oxide synthase coupling may provide a useful therapeutic target for treating patients with colorectal cancer.